Panorama de la premsa comarcal en català a les terres de l'Ebre (1900-1936). - DEL CARME GOMBAU DOMINGO, MARIA (Scripta, 2017)
In the middle of a journalistic circuit written exclusively in Spanish, comes the first newspaper written entirely in Catalan in the city of Tortosa: La Veu de Tortosa. This one is followed by La Veu de la Comarca which has the firm intention of «awake the Catalan consciousness of the district of Tortosa». Both newspapers represent the introduction of regionalism in Terres de l' Ebre and the Catalan language in a zone dominated throughout the first decade of the twentieth century by Spanish dynastic parties. After the silence of the dictatorship of Primo de Rivera appears a homonymous weekly as a diffusion platform of a district party related to the Lliga Regionalista. In counterpart, the magazine Vida Tortosina first, and the biweekly Acció after, become organs of expression of Acció Catalana and represent a moderate progressive nationalism. Regionalists and nationalists tried to fight the greatest political force in Tortosa with the establishment of the II Republic, the «marcel·linistes» Republicans.